Сравнительный анализ двух однофазных высокоскоростных машин с магнитами на статоре - Прахт, Владимир Алексеевич; Дмитриевский, Владимир Алексеевич; Казакбаев, Вадим Маратович; Ошурбеков, Сафарбек Хосабекович (Національний технічний університет "Харківський політехнічний інститут", 2020)
Цель. Исследование характеристик двух высокоскоростных однофазных электрических машин с магнитами на статоре (электрическая машина с переменным направлением потока и гибридная вентильно-индукторная реактивная машина): сравниваются такие характеристики как КПД, вес, стоимость активных материалов, номинальный ток элементов преобразователя частоты. Методика. Расчет характеристик электрической машины с помощью решения двухмерных краевых магнитостатических задач. Результаты. Произведено сопоставление двух типов однофазных машин с магнитами на статоре; получено расчетное сравнение характеристик однофазной электрической машины с переменным направлением потока и однофазной гибридной вентильно-индукторной реактивной машины; получены результаты сравнения массы и размеров КПД двух машин. Научная новизна. Впервые получены результаты сравнения однофазной электрической машины с переменным направлением потока и однофазной гибридной вентильно-индукторной реактивной машины. Практическое значение. Полученные результаты могут помочь при выборе лучшей конструкцией электродвигателя в рассматриваемых приложениях: электрический турбонаддув, бытовые приборы, вентиляторы, насосы и компрессоры малой мощности и т.д.

Purpose. Single-phase machines with permanent magnets on the rotor are widely used in a variety of applications of a low rated power. When these machines are applied in high-speed applications, a retaining ring on the rotor core must be often used. However, it makes the assembly more complex and the high-speed machines become more expensive. On the other hand, machines with magnets on the stator still can be a valuable alternative due to their simple and reliable rotor design. In this paper the comparative study of performances of two single-phase electrical machines with magnets on the stator (flux reversal electrical machine and hybrid switched reluctance machine) is presented. The following performances have been compared: efficiency, weight, active materials cost, value of rated current of switches of the frequency converter. Methodology. Calculation of electrical machines performances using solving two-dimension boundary magnetostatics problems. Results. The theoretical comparison of the flux reversal electrical machine and the hybrid switched reluctance machine has been carried out; the comparison on specific torque and efficiency of the two aforementioned machines have been obtained. The flux reversal machine has a significantly higher efficiency and a fewer weight. In addition, it has a lower value of rated current. On the contrary, the cost of active materials of the hybrid switched reluctance one is much less. Originality. The presented results can assist in selecting the best design alternative of electrical machines in the following applications: electrical blowers, household appliances, fans, pumps and compressors of a low rated power etc. Practical value. The comparisons results of the flux reversal electrical machine and the hybrid switched reluctance machine has been obtained for the first time.
Comparative analysis of two high-speed single-phase electrical machines with permanent magnets on the stator
Keywords: однофазные электрические машины; гибридные вентильно-индукторные реактивные машины; высокоскоростные электрические машины; магнитная индукция; импульсы напряжения; роторы; магниты; high speed machines; hybrid switched reluctance machine; flux reversal electrical machine; permanent magnet machine; special electrical machine